Ultrasonic inline inspection of a cement-based drinking water pipeline. (1st May 2020) - Hernandez Delgadillo, Hector; Geelen, Caspar; Kakes, Rutger; Loendersloot, Richard; Yntema, Doekle; Tinga, Tiedo; Akkerman, Remko
Highlights: Estimation of degradation levels in a cement-based pipeline. The extent of degradation along the inspection trajectory is consistent. The extent of degradation along the circumference differs. The speed of sound in cement has the highest sensitivity for estimating the degradation levels. Abstract: The integrity of the drinking water infrastructure deteriorates with time. Monitoring the condition of the drinking water mains can enhance the remaining operational lifetime assessment of the network. In this research a method to translate ultrasonic signals to degradation levels from an inline inspection in a cement-based drinking water pipeline is proposed. The data was obtained from an inspection performed in a Dutch drinking main section. The data is processed in two major steps. Firstly, the parameters that provide the condition of the cement are extracted. Secondly, images of the degradation within the pipes of the inspected trajectory were generated. The main contributions in this paper are (i) the estimation of relative degradation levels of a cement-based pipeline based on the ultrasonic pulse-echo technique and (ii) the upscaling of the processing method in an automated manner for visualization of the degraded condition. Lastly, a sensitivity study of the parameters relevant to the determination of the degraded depth has been performed. The speed of sound in cement is the most relevant parameter to consider. Estimating absolute degradation levels needs further study.